Remote learning during the COVID-19 pandemic in the opinion of academic teachers. Survey research - Mlodawski, Jakub; Swiercz, Anna; Mlodawska, Marta; Piąta, Aleksandra; Swiercz, Grzegorz; Gawdzik, Barbara (Journal of Education, Health and Sport, 2022)
During the COVID-19 pandemic, the academic community had to drop out of the full-time on-site education and switch to distance learning. After two years of this state of affairs and the current return to the traditional form, we would like to explore the opinions of academic teachers on this form of teaching. The study was a questionnaire-based survey, including 86 teaching staff members of the Jan Kochanowski University of Kielce, working at four faculties. The teachers assessed the level of distance learning as average, no different from the traditional approach. However, they pointed out that the involvement, activity of students, regularity of work, quality of the assignments completed, and the adequacy of the grades received is greater in the traditional approach. In the case of remote learning, in the group’s assessment, the timeliness of performing the assignments had not deteriorated. The most frequently indicated advantage of remote learning was time saving, while the most common disadvantage was reduced contact with students. In the teachers’ opinion, the traditional mode of learning still has an advantage over distance learning. Studies assessing effectiveness in achieving educational goals are needed in order to objectify the results.